ChemInform Abstract: Ln(IO3)3 (Ln: Ce, Nd, Eu, Gd, Er, Yb) Polycrystals as Novel Photocatalysts for Efficient Decontamination under Ultraviolet Light Irradiation. Issue 29 (22nd July 2014) - Wang, Wenjun; Cheng, Hefeng; Huang, Baibiao; Li, Xinru; Qin, Xiaoyan; Zhang, Xiaoyang; Dai, Ying
Abstract Ln(IO3)3 (Ln = Ce, Nd, Eu, Gd, Er, Yb) polycrystals are hydrothermally prepared using aqueous solutions of Ln(NO3)3 or Ln2O3 and HI as precursors (autoclave, 230 °C, 24 h).